Pemutakhiran Data Kependudukan, Penyesuaian Layanan Surat Menyurat, Dan Pembuatan Panduan Penggunaan Layanan Sistem Informasi Desa Keramas - Karyada, I Kadek Mahendra; Wijaya, I Nyoman Yudi Anggara; Putra, I Gede Juliana Eka (AJAD : Jurnal Pengabdian kepada Masyarakat, 2025)
The use of technology and information systems has become one of the most effective means of disseminating information in the modern era. One implementation of technology and information systems in village government is through village websites. Keramas Village, a region in Bali Province, is an example of how implementing a website-based information system can improve services to the community. However, obstacles related to database optimization and website usage guidelines are still a concern. This research aims to overcome this problem by optimizing the database in the Village Information System using OpenSID and compiling a guide for using the Keramas Village website. Through data collection, improving correspondence services, and creating guide books and videos, it is hoped that the Keramas Village website can be more effective in providing information and public services to its community. Program evaluation will ensure successful implementation as well as uncover areas for further improvement. Thus, this research not only provides practical benefits for Keramas Village and its community but also enriches the author's technical and analytical skills in data management and guide preparation.